Modelling And Analysis Of New Double Stator Slotted Rotor Permanent Magnet Machine - Che Ahmad, Suhairi Rizuan (2019)
Over the past few years, the usage and demand of permanent magnet machine were very high due to its high power density and high efficiency. There are many stator topologies used in designing permanent magnet machine such as double stator topology. The main constraint of the double stator topology is to maintain its mechanical air gap between the inner and outer stator. A significantly large air gap was noted because the rotor was made from non-ferromagnetic material that led to uneven flux distribution. The second issue refers to the complex design of the double stators that shared similar magnetic and mechanical structures. They required more computational time in designing the double stators. Most researchers have looked into the design of electrical machine for either motor or generator. However, a few of them has investigated the motor-generator mode configurations. This thesis discussed the modelling and analysis of a new double stator slotted rotor permanent magnet machine (DSSR-PMM). A new slotted rotor from ferromagnetic material was used for the double stators in order to maximise the flux produced by the permanent magnet and coil by reducing flux leakage. The implementation of slotted rotor optimised the magnetic flux and evenly distributed the air gap of the inner and outer stator. The Permeance Analysis Method (PAM) for modelling the sizing equation of DSSR-PMM reduced computational time. The PAM formulated the sizing equation to calculate the magnetic flux of air gaps in the inner and outer stator. The performance of the DSSR-PMM under motor-generator mode was analysed in three main condition systems i.e. motoring mode, generating mode and motor-generator modes. In the motoring or generating mode configurations, both inner and outer stator served as the motor or generator or vice-versa. In this research, the numerical design used finite element method (FEM) to validate PAM. The FEM was also used to analyse the characteristics of flux linkage, back EMF, and inductance. For further validation, a prototype of DSSR-PMM was fabricated and tested with various loading conditions to derive the electromagnetic torque, the output power, and the efficiency for the proposed structure. The results from FEM and measurement were verified and they appeared to be in good agreement. The highest efficiency and torque had been achieved by using motoring mode of 94 % and 16.2 Nm respectively. The generating mode showed consistent efficiency value with maximum power and efficiency of 1000 W and 75% respectively. As for the motor-generator mode, the DSSR-PMM showed simultaneous performance as the motor and the generator depended on primary and secondary modes. In motor-generator mode displayed similarity in graph pattern for torque, efficiency, input, and mechanical power. For benchmarking purpose, the proposed DSSR-PMM exhibited 19% higher percentage of power density, when compared to the previous double stator structure. It was discovered that the flux linkage and back EMF was increased by 50% and 46% when the double stator slotted rotor structure implemented in comparison to the single stator topology with the same design structure. The output torque was increased as the structure has two air gaps in the inner and outer stators which was advantageous to the DSSR-PMM in motoring mode. The efficiency of DSSR-PMM in generating mode was maintained as the speed of generator was increased. As for advantage the DSSR-PMM can operate in wider operating speeds and loads. The details on individual losses, a use of optimum power driver circuit and the fabrication cost of DSSR-PMM need to consider for future research. This thesis offers guidelines for designing and analysing DSSR-PM machine.